PENGARUH KEMUDAHAN PENGGUNAAN, KEAMANAN DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA GRAB DI KOTA BATAM - Adek Ali Azhar; Sunarto Wage (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
This research aims to analyze the influence of ease of use, security and brand image on purchasing decisions for Grab services in Batam City. This type of research is descriptive with a quantitative approach, with the population using the Grab application in Batam City in 2024 which cannot be known with certainty. The sampling technique used the Lameshow formula to produce 100 respondents drawn using purposive sampling. Data analysis was carried out using multiple linear regression techniques to carry out data quality tests, classical assumption tests, influence tests, and hypothesis tests. This research found that ease of use, security, and brand image have a positive and significant influence on purchasing decisions. The calculated t value for ease of use is 3.122 with a significance of 0.002, for security it is 4.991 with a significance of 0.000, and for brand image it is 6.672 with a significance of 0.000, all of which exceed the t table value of 1.984 and are below the significance threshold of 0.05, supporting hypothesis H1 , H2, and H3. In addition, simultaneous analysis shows that the calculated f value of 102.955 exceeds the f table value of 2.70 with a significance of 0.000, supporting Ha's hypothesis that ease of use, security and brand image simultaneously have a positive and significant effect on purchasing decisions